Design and analysis of shell and tube heat exchanger - Fernandes Erica Jacqueline; Krishanmurthy Sachidananda Hassan (International Journal for Simulation and Multidisciplinary Design Optimization, 2022)
The demand for consumption of energy in industries has made designers to build efficient heat transfer exchangers. One of the most used heat exchangers which supports this is the shell and tube heat exchangers which are built for effective heat transfer. These heat exchangers are widely utilized in the HVAC industries especially in chiller plants due to their large surface for heat transfer. So, design of these chillers is influenced by the selection of material. This research paper discusses the design and analysis of shell and tube heat exchangers by considering different material and their ability to transfer heat from the surface. So, baffles play an important role to analyze the performance of the heat exchangers and it is possible to improve their heat transfer capabilities. So, in this research paper baffle spacing and its effect on heat transfer has been analyzed using CFD analysis and compared these results with the theoretical analysis. The Design and modelling of the heat exchanger have been modelled using PTC Creo parametric and using ANSYS Fluent CFD analysis have been carried out considering copper, aluminum, and steel as the materials. From this analysis it can be stated that copper has performed well as compared to aluminum and steel by using minimum baffle spacing.